Personality modification by a cognitive-behavioral therapy of stress coping. - Linares-Ortiz, Julia; Robles-Ortega, Humbelina; Peralta-Ramírez, Maria I. (Anales de Psicología / Annals of Psychology, 2013)
The objective of this study was to assess the possibility of varying personality variables (such as some of the Big Five factors, or hardiness) through the application of a stress doping therapy. Twenty-six people participated from universities with high perceived stress, divided into two groups (treatment group and control group). The assessment instruments selected were classified into two groups: psychological and emotional variables and personality variables.The results showed that after the program, the experimental group showed a decline in scores of stress, psychopathology and worries. On the other hand, personality variables, interaction was found in the variables moment x group, optimism, extraversion factor and accountability, corresponding to the model of the Big Five factors showed increased scores on these variables. However, these changes were not in the control group. The hardy personality scores did not change in either group. This study tests the modulation of certain factors of personality through cognitive-behavioral therapy for stress management, after which beneficial effects are obtained.